A study of resilience in relation to extraversion and decision-making styles of management students. - Quimpo, Ruth Gail E (2015.)
The study investigated the relationship betwee extraversion, decision-making style and resilience among management students. The study also looked into the four decision-making styles to check whether there is a decision-making style that had a significant relationship with resilience as well as a significant difference among the levels of resilience between the individuals with the different decision styles. To examine these relationships, 92 management students from two universities in Iloilo were taken as respondents for this study. An Introversion scale was used to measure the extraversion of the respondents. A resilience scale was used to measure their resilience and the Decision-style Inventory was used to detemine the decision-making styles of the respondents., Using the Pearson's Product Moment Correlation, the researcher found that no relationship exists between extraversion and resilience. With the same statistical tool, the results showed a positively moderate significant relationship between the Directive decision-making style and resilience. Using the Kruskall-Wallis H Test, a nonparametric test, it was found that there is a significant difference among the levels of resilience between the respondents.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Students -- Management